The power of trichlorosilylation: isolable trisilylated allyl anions, allyl radicals, and allenyl anions. Issue 37 (24th August 2021) - Georg, Isabelle; Bursch, Markus; Endeward, Burkhard; Bolte, Michael; Lerner, Hans-Wolfram; Grimme, Stefan; Wagner, Matthias
Abstract : Treatment of hexachloropropene (Cl2 CC(Cl)–CCl3 ) with Si2 Cl6 and [ n Bu4 N]Cl (1 : 4 : 1) in CH2 Cl2 results in a quantitative conversion to the trisilylated, dichlorinated allyl anion salt [ n Bu4 N][Cl2 CC(SiCl3 )–C(SiCl3 )2 ] ([ n Bu4 N][1 ]). Abstract : Treatment of hexachloropropene (Cl2 CC(Cl)–CCl3 ) with Si2 Cl6 and [ n Bu4 N]Cl (1 : 4 : 1) in CH2 Cl2 results in a quantitative conversion to the trisilylated, dichlorinated allyl anion salt [ n Bu4 N][Cl2 CC(SiCl3 )–C(SiCl3 )2 ] ([ n Bu4 N][1 ]). Tetrachloroallene Cl2 CCCCl2 was identified as the first intermediate of the reaction cascade. In the solid state, [1 ] − adopts approximate C s symmetry with a dihedral angle between the planes running through the olefinic and carbanionic fragments of [1 ] − of CC–Si//Si–C–Si = 78.3(1)°. One-electron oxidation of [ n Bu4 N][1 ] with SbCl5 furnishes the distillable blue radical 1 ˙. The neutral propene Cl2 CC(SiCl3 )–C(SiCl3 )2 H (2 ) was obtained by (i) protonation of [1 ] − with HOSO2 CF3 (HOTf) or (ii) H-atom transfer to 1 ˙ from 1, 4-cyclohexadiene. Quantitative transformation of all three SiCl3 substituents in 2 to Si(OMe)3 (2 OMe ) or SiMe3 (2 Me ) substituents was achieved by using MeOH/NMe2 Et or MeMgBr in CH2 Cl2 or THF, respectively. Upon addition of 2 equiv. of t BuLi, 2 Me underwent deprotonation with subsequent LiCl elimination, 1, 2-SiMe3 migration and Cl/Li exchange to afford the allenyl lithium compound Me3 Si(Li)CCC(SiMe3 )2 (Li[4 ]), which is an efficient building block for the introduction of Me, SiMe3, or SnMe3 (5 ) groups. The trisilylated, monochlorinated allene Cl3 Si(Cl)CCC(SiCl3 )2 (6 ), was obtained from [ n Bu4 N][1 ] through Cl − -ion abstraction with AlCl3 and rearrangement in CH2 Cl2 (1 ˙ forms as a minor side product, likely because the system AlCl3 /CH2 Cl2 can also act as a one-electron oxidant).